The Oxford handbook of strategic sales and sales management - Cravens, David W.; Le Meunier-FitzHugh, Kenneth.; Piercy, Nigel. (Oxford University Press, 2011)
'The Oxford Handbook of Strategic Sales and Sales Management' is a comprehensive overview of the latest research in the area by leading international academics. The handbook is suitable for academics, professionals, and those taking professional qualifications in sales and marketing.